Digital Skill Moderation in the Relationship between Digital Exploitation Capability and Transformation Performance - Sutrino, Anas; Putri, Triwulandari Nehru; Masse, Ambo; Nurvianti, Nurvianti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Digital transformation is a strategic issue for micro, small, and medium enterprises (MSMEs) in the face of the dynamics of an increasingly competitive business environment. This study aims to analyze the influence of digital exploitation capability, strategic agility, and digital skills on transformation performance, as well as test the role of digital skills as a moderation variable in the relationship between digital exploitation capability and transformation performance. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data was collected through a structured questionnaire from 233 MSME owners in Kendari City. The descriptive results show that the majority of respondents have a high level of education, dominated by women, and are of productive age, which indicates cognitive and adaptive readiness for digital transformation. The findings of the study show that digital exploitation capability, strategic agility, and digital skills play an important role in driving the transformation performance of MSMEs. In addition, digital skills have been proven to strengthen the effectiveness of digital exploitation capabilities in producing more optimal transformational performance. This research provides a theoretical contribution by strengthening the perspective of dynamic capability in the context of MSMEs, as well as practical implications for the development of policies and strategies to improve the digital capabilities of MSMEs in developing regions.